Application of neutron imaging to detect and quantify fatigue cracking. (August 2019) - Reid, A.; Marshall, M.; Kabra, S.; Minniti, T.; Kockelmann, W.; Connolley, T.; James, A.; Marrow, T.J.; Mostafavi, M.
Highlights: Neutron transmission imaging can successfully measure in situ elastic strains. For duplex steels strain is measured more accurately in ferrite than austenite. X-ray and neutron computed tomography can visualise the profile of a fatigue crack. Neutron tomography can differentiate between the phases in a dual phase sample. Abstract: Non-destructive imaging techniques provide a unique opportunity to study crack initiation and propagation behaviour in structural materials. To evaluate the applicability of different volumetric imaging techniques, a round bar notched sample of duplex stainless steel was fatigue cracked and studied in situ and ex situ. Neutron and synchrotron X-ray tomography was used along with destructive methods and Bragg edge neutron imaging to evaluate the fatigue crack. Neutron attenuation tomography obtained a three-dimensional image in which the crack was readily identifiable. The neutron tomography, although lower in spatial resolution compared with the X-ray synchrotron tomography and requiring higher acquisition time, is sensitive to the phase chemistry, and has the potential to study engineering size components. Bragg edge neutron transmission imaging allows for the mapping of two-dimensional elastic strains and was used to identify the fatigue crack from the reduction in the strain in the region where the crack propagated. A finite element model of the cracked specimen was used to simulate the average through thickness strain that is measured by the Bragg edge neutron imaging technique. The strains measured in the ferritic phase correspond better with the simulation strains than the strain measured in the austenitic phase. It is concluded that this difference is due to strain partitioning, which is influenced by the strong texture present in the duplex steel. Graphical abstract: Image, graphical abstract